Medieval Renaissance Baroque: A Cat's Cradle for Marilyn Aronberg Lavin - Lavin, Marilyn Aronberg; Levine, David A.; Freiberg, Jack (Italica Press, 2010)
"Reflects Marilyn Aronberg Lavin's innovative work in art and cultural history in both the print and digital realms. Contributors: Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, Gary Schwartz. Seventy-seven illustrations, bibliography of Lavin's works, index"–Provided by publisher.
Keywords: Art; European; dept.art; faculty_collection

Casablanca on the Moon - Phelan, William R. (Createspace, 2010)
Keywords: dept.art; faculty_collection

Landscapes of order, landscapes of memory: Italian-American residential landscapes of the New York metropolitan region - Inguanti, J.J. (Italian Folk: Vernacular Culture in Italian-American Lives, 2010)
In June of 2004, The New York Times reported that the fig trees in the Carroll Gardens section of Brooklyn were dying.1 Accompanying this horticultural death was another transition. Like the fig trees, the elderly Italian-American people who tended them were also gradually disappearing from the neighborhood. The article demonstrated what most residents of the New York tri-state area already knew: The ethnic make-up of a neighborhood often may be "read" through the residential landscape choices of its inhabitants. For people of Italian descent, the fig tree (Ficus carica) is one of many ethnically significant components of the landscape. Throughout the New York City metropolitan region, the residential landscape plays a prominent role in the construction of Italian-American identity. With their symmetrical plans, sheared shrubs, religious statues, and fig trees, Italian-American landscapes proclaim the ethnicity of homeowners and knit neighborhoods together with a shared horticultural and design idiom. Despite the facility with which the denizens of the New York tri-state region discern and describe this "Italian look," no study concerned primarily with the visual analysis and historical precedents of these Italian-American residential landscapes yet exists. Copyright © 2011 Fordham University Press. All rights reserved.
Journal Abbreviation: Ital. Folk: Vernac. Culture in Ital.-Amer. Lives
Keywords: dept.art

Medieval Renaissance Baroque: A Cat's Cradle in Honor of Marilyn Aronberg Lavin - Levine, David A.; Freiberg, Jack (Italica Press, Inc., 2010)
"Medieval renaissance Baroque" celebrates Marilyn Aronberg Lavin's breakthrough achievements in both the print and digital realms of art and cultural history. Fifteen friends and colleagues present tributes and essays that reflect every facet of this renowned scholar's brilliant career. Tribute presenters include Ellen Burstyn, Langdon Hammer, Phyllis Lambert, and James Marrow. Contributors include Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, and Gary Schwartz. 79 illustrations, bibliography of Marilyn Lavin's works, index.
Keywords: dept.art

“Urbs Aeterna” and Dutch Painting of Roman Ruins - Levine, David A. (Medieval Renaissance Baroque: a cat's cradle for Marilyn Aronberg Lavin, 2010)
"Reflects Marilyn Aronberg Lavin's innovative work in art and cultural history in both the print and digital realms. Contributors: Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, Gary Schwartz. Seventy-seven illustrations, bibliography of Lavin's works, index"–Provided by publisher.
OCLC: 423389186
Keywords: dept.art